Ischaemic events are rare, and the prevalence of hypertension is not high in Japanese adults with haemophilia: First multicentre study in Asia. Issue 4 (2nd May 2019) - Nagao, Azusa; Suzuki, Nobuaki; Takedani, Hideyuki; Yamasaki, Naoya; Chikasawa, Yushi; Sawada, Akihiro; Kanematsu, Takeshi; Nojima, Masanori; Higasa, Satoshi; Amano, Kagehiro; Fukutake, Katsuyuki; Fujii, Teruhisa; et al.
Abstract : Introduction: With the increasing life expectancy of patients with haemophilia (PWH), the number of PWH with age‐related comorbidities, such as ischaemic events, is increasing. Aim: We conducted this multicentre observational study to identify the risk factors for major ischaemic events in PWH. Methods: This study was the first multicentre observational study, conducted with the participation of five haemophilia treatment centres in Japan, conducted in ≥30‐year‐old adult PWH. The latest data recorded in the medical charts between 1 January and 31 December 2016 were reviewed. Healthcare data collected from the National Health and Nutrition Survey were used as the control data. Results: Data of a total of 711 patients were collected. Only two PWH (0.3%) had a history of ischaemic events. Age‐adjusted analysis indicated that the prevalence of hypertension defined as a blood pressure of 140/90 mm Hg or over was similar in the PWH to that in the males of the general population. However, when hypertension was defined more strictly (≥130/85 mm Hg), the prevalence was significantly lower in PWH than in the general male population. The hypertension in PWH was associated with the age, BMI, CKD, HIV infection and inhibitors. In particular, the odds ratio for the presence of inhibitors was high (odds ratio = 7.529). Conclusion: Whether the present results can be attributed to Japanese ethnicity or to the presence of haemophilia per se remains uncertain. We propose to initiate a prospective study for further investigation.